Supported SnS2 Nanosheet Arrays on Ni Foam for Supercapacitors - Sun, Haibin; Liang, Shuangshuang; Zheng, Wenrui; Liu, Congcong; Zhang, Chao; Ji, Zhichao; Liu, Shenghong; Xie, Wenhe (Frontiers in Energy Research, 2022)
Layered metal sulfides are regarded as potential candidates for supercapacitive electrode materials due to the unique spatial dimensions for charge transport. Herein, self-supported SnS2 nanosheet arrays on nickel (Ni) foam were successfully fabricated via a facile solvothermal approach. Interestingly, the continuous and high-density SnS2 nanosheet arrays are interconnected to form porous Ni@SnS2 electrode materials, which suppress the self-aggregation of SnS2 and provide outstanding conductivity with 3D-networked Ni framework. The Ni@SnS2 electrode demonstrates a high areal specific capacitance of 1965.56 mF cm−2 at a current density of 1 mA cm−2 and satisfactory cycling stability (78.3% capacity retention after 10,000 cycles). This self-supported porous structure provides a promising way to build advanced electrode material for supercapacitors.